2015
DOI: 10.3390/en8065704
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Surface Wettability and Roughness on the Heat Transfer Performance of Fluid Flowing through Microchannels

Abstract: Abstract:The surface characteristics, such as wettability and roughness, play an important role in heat transfer performance in the field of microfluidic flow. In this paper, the process of a hot liquid flowing through a microchannel with cold walls, which possesses different surface wettabilities and microstructures, is simulated by a transient double-distribution function (DDF) two-phase thermal lattice Boltzmann BGK (LBGK) model. The Shan-Chen multiphase LBGK model is used to describe the flow field and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…The high amount of roughness is unwanted and would be expensive to produce. This also gives undesirable properties for the manufacturing of hydrophobic coating, which in general have very smooth surface characteristics (5). This research focused on the fabrication of superhydrophobic/hydrophobic nanocomposites coating by electrospinning technique and aimed to study the surface morphology of coated surface.…”
Section: Figure 1 Ranges Of Contact Anglementioning
confidence: 99%
“…The high amount of roughness is unwanted and would be expensive to produce. This also gives undesirable properties for the manufacturing of hydrophobic coating, which in general have very smooth surface characteristics (5). This research focused on the fabrication of superhydrophobic/hydrophobic nanocomposites coating by electrospinning technique and aimed to study the surface morphology of coated surface.…”
Section: Figure 1 Ranges Of Contact Anglementioning
confidence: 99%
“…Surface roughness define the changes alteration on coated substrate and how react to the ambient environment, higher roughness value is undesirable, hard and expensively to control the product. Also granted unwanted properties for the fabrication of hydrophobic coating which generally known that owns very smooth surface properties [4]. Hardness is the resist of surface deformation produced by indentation and shows how surface can interact to the environmental situation and defect that can stick and arise with its properties.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies showed that conventional fluid dynamics theories are generally applicable in microchannels fluid flow analysis [8,9]. However, due to the small size of the microchannel, parameters such as surface roughness and wettability of their walls can cause differences in the way fluid flows in larger-scale channels [10][11][12]. Another factor that can add to studying fluid flow in microchannels, especially in biological systems, is the inherent complexity of biological fluids.…”
mentioning
confidence: 99%